Analysis of the Development of Fashion Trends: A Bibliometric Study - Sifa Sifa; Sri Endah Wahyuningsih (Universitas Negeri Semarang, 2026)
The development of fashion trends reflects social, economic, technological, and environmental changes within the global fashion industry. As the complexity of these issues increases, academic research on fashion trends has shown significant growth and has become increasingly multidisciplinary. This study aims to map publication trends, intellectual structures, and dominant themes in fashion trend research using a bibliometric approach. The research data were obtained from the Scopus database covering the period 2016–2025. Through a literature selection process based on PRISMA guidelines, a total of 155 journal articles were analyzed using VOSviewer software. The analysis includes publication trends, co-authorship, keyword co-occurrence, co-citation, and bibliographic coupling. The results indicate a significant increase in the number of publications since 2021, peaking in 2024. The United States and China are identified as the main contributors, supported by institutions focusing on management, economics, and manufacturing technology. Keyword analysis reveals that sustainability, circular economy, consumer behavior, and digital technology integration are dominant themes. However, collaboration and co-citation networks indicate that the research structure remains relatively fragmented. These findings highlight the importance of strengthening interdisciplinary collaboration and conceptual integration in fashion trend research.